The geography of a rapid rise in elderly mortality in England and Wales, 2014-15 - Green, M; Dorling, D; Minton, J (Elsevier, 2017)
Since at least the early 1900s almost all affluent nations in the world have continually experienced improvements in human longevity. Using ONS mid-year population and deaths estimates for Local Authorities for England and Wales, we show that these improvements have recently reversed. We estimate that in England and Wales there were 39,074 more deaths in the year to July 2015 as compared to the year to July 2014 (32,208 of these were of individuals aged 80+). We demonstrate that these increases occurred almost everywhere geographically; in poor and affluent areas, in rural and urban areas. The implications of our findings are profound given what has come before them, combined with the current political climate of austerity.